2021
DOI: 10.1177/1534734621992290
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity, Antibiotic Resistance, and the Risk of Lower Limb Amputation in Younger and Older Individuals With Diabetic Foot Infection

Abstract: Introduction A diabetic foot infection (DFI) contributes to high mortality and morbidity in diabetics due to its often rapid progressive and intricately treatable infection. DFIs are usually a polymicrobial infection and characterizing the entire bacterial load is still challenging. Prompt and effective treatment of DFI is nevertheless mandatory to safe limbs and lives. It is therefore crucial to know the local pathogen spectrum and its antibiotic susceptibility. Methods and Material For a 12-month period, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Diabetic skin has been shown to have higher colonization of both S. aureus and S. epidermidis [ 74 ]. A recent analysis of German patients with DFUs identified Staphylococcus, Pseudomonas, and Enterobacteriaceae as the most common bacterial colonizers [ 76 ]. When stratifying DFUs by infection severity, a recent study identified Staphylococcus and Streptococcus as the most abundant species in mildly to moderately infected DFUs, while more severely infected DFUs had increased bacterial diversity [ 77 ].…”
Section: Pathophysiology Associated With Diabetic Wound Healingmentioning
confidence: 99%
“…Diabetic skin has been shown to have higher colonization of both S. aureus and S. epidermidis [ 74 ]. A recent analysis of German patients with DFUs identified Staphylococcus, Pseudomonas, and Enterobacteriaceae as the most common bacterial colonizers [ 76 ]. When stratifying DFUs by infection severity, a recent study identified Staphylococcus and Streptococcus as the most abundant species in mildly to moderately infected DFUs, while more severely infected DFUs had increased bacterial diversity [ 77 ].…”
Section: Pathophysiology Associated With Diabetic Wound Healingmentioning
confidence: 99%
“…DFU is a risk factor for lower extremity amputations, especially in cases of infections caused by MDR bacteria 43,44 . Among gram‐negative bacilli, PA is the predominant causative bacterium of DFIs, 45 21% of which are MDR bacteria 6 . Additionally, PA efficiently produces strong biofilms capable of impeding wound healing and reducing the effectiveness of antimicrobial drugs 46 .…”
Section: Discussionmentioning
confidence: 99%
“…One-half of major (above-or below-knee) lower extremity amputations in people with diabetes are due to microbial infection. 7,25 Flowchart depicting the pathophysiology of diabetic foot ulcer is given in Figure 1.…”
Section: Pathophysiology Of Diabetic Foot Ulcermentioning
confidence: 99%